Pengaruh Disiplin Terhadap Kinerja Karyawan Pada PT PLN (PERSERO) Area Merauke - Dewi Putri Anjar Wulan (Musamus Journal of Business & Management, 2018)
This study aims to determine the effect of discipline on the performance of employees of PT PLN (Persero) Merauke Area. The sample in this study were 52 respondents, the sampling method used was the technique of total sampling and sampling was done using a Likert Scale, then the data was processed using SPPS version 17 with a simple linear regression analysis technique. From the regression analysis obtained by the equation Y = 26.133 + 0.269 (X). Hypothesis testing using the t test shows that the discipline variable (X) is proven to have a significant effect on employee performance (Y), this is evidenced by the value of t count, (X) = 3.070 with a significant level of 0,000 <0.5 so ha is accepted and ho is rejected. R Square figures of 15.9% indicate that employee performance can be explained by disciplinary variables, while 84.1% is explained by other variables not examined in this study. Keywords: Discipline and Employee Performance.